Price Perception Optimization Strategy to Increase Purchasing Decisions for Flash Sale Products in the Shopee Application - Hayati, Fitri; Yafiz, Muhammad; Lubis, Adrian Niken; Tama, Aria Satria (Universitas Islam Negeri Sumatera Utara, 2024)
Technological advancements and the widespread use of the internet have changed consumer behavior in Indonesia, with e-commerce becoming an integral part of everyday transactions. This study examines optimizing price perception to improve purchase decisions for flash sale products on Shopee, a major e-commerce platform in Indonesia. It involves Focus Group Discussions, Training, and Collaboration with government entities to explore the impact of price perception on consumer choice. A sample of 150 Shopee users and 50 sellers was analyzed to assess the effectiveness of price perception strategies. The results showed that, although promotions such as discounts and flash sales attract attention, clear and honest price perception influences purchasing behavior significantly. Training sessions revealed that transparency and accurate discount information increased consumer trust, increased engagement in flash sales and seller profits. The study concludes that optimizing price perception through effective promotional strategies is critical in competitive e-commerce. A balance between attractive prices and perceived value can drive consumer loyalty and market competitiveness.